Leveraging Commercial and Other Innovation for Future U.S. Navy Data Warfare Needs - Johnson, Burnadette; Barber, Arthur; Crawford, Gregory; Llorens, Ashley J.; Medicine, National Academies of Sciences, Engineering, and (The National Academies Press, 2020)
At the request of then-Chief of Naval Operations Admiral John Richardson, the National Academies of Sciences, Engineering, and Medicine appointed an expert committee to study the extent to which state-of-the-art data science, data analytics, networking, communications, and architecture approaches could be potentially applied to broader U.S. Naval Forces' "decision space" needs to ensure that the speed and flexibility of the Navy's decision-making process is better than that of its potential adversaries. The Department of the Navy has determined that the full report prepared by the Committee on Maintaining Operational Effectiveness for U.S. Naval Forces in Highly Degraded Environments—Phase 1 is subject to Department of Defense (DoD) Distribution Statement D: Release Restricted to DoD and DoD Contractors.